Halal Tourism Policy: is a New Wave in Development Tourism in West Sumatera - Koeswara, Hendri; Febryandanda, Noversa; Rahman, Riki (Jurnal Administrasi dan Kebijakan Publik, 2024)
West Sumatra also has Adat Basandi Syara', Syara' Basandi Kitabullah, Syara' Mangato Adat Mamakai use which is guidelines life Minangkabau people. With stipulated Boast as destination world halal tourism. Boast in a manner No direct get evaluation to image halal tourism, however visit foreign tourists to boast no experience improvement. Because of it, Government Boast through the Tourism Office Province Boast with the provincial legislature Boast as well as team expert from academics and LPPOM-MUI West Sumatra initiative make regulation maintenance halal tourism so that halal tourism in West Sumatra has print clear and strong blue so that tourists come travel No forget worship. Method used in study This is descriptive qualitative. Data collection techniques used in this study is interview, observation, and documentation. Study This use approach formulation policy in do analyze to policy this halal tourism. The results of this study can found that policy tourist is a new direction policy tourism in West Sumatra, but it must need more effective strategy the reach the purpose of this policy. This no just implicated to guarantee to guaranteed public in do tour but more to enhancement economy and welfare visible society with an increase number visit tour.